OPTIMIZATION OF PIA CAKE PRODUCTION TIME USING THE HUNGARIAN METHOD (CASE STUDY: IBU WA NINA UMKM) - Rumetna, Matheus Supriyanto; Ninia Lina, Tirsa; Latupeirissa, Valentino; Sampe Lidan, Jesika; Stevanio Insosanta Makatita, Margrio; Dewi, Dewi; Kota, Oktovianus; Maria Kewetary, Meita; Syufan, Marselino (Journal of Computer Science and Technology (JCS-TECH), 2024)
This research aims to optimize the production time for Pia Cakes in Mrs. Wa Nina's business using the Hungarian Method. The problem faced was that production took up to 9 hours every day with three employees who had different work responsibilities. The Hungarian method, developed by D. Konig, Harold Kuhn, and James Munkres, is applied to optimize the distribution of tasks based on employee abilities and experience, thereby reducing variations in processing time and increasing productivity. The POM-QM for Windows application is used for critical analysis and planning of production and distribution processes. The research results show that by using the Hungarian Method and POM-QM for Windows, production time can be minimized and operational efficiency increased significantly, namely 450 minutes or 7 hours 30 minutes. This implementation also helps in planning more efficient production schedules and better meeting market demands.